Scalable fabrication of single- and multi-layer planar lenses on fiber imaging probes - Fei He; Rafael Fuentes-Domínguez; Richard Cousins; Christopher J. Mellor; Andrew Daniel Rocha; Zuzana Adams; Jennifer K. Barton; George S. D. Gordon (APL Photonics)
We present a novel, scalable method for fabricating single- and multi-layer planar lenses on 125 μm-diameter fiber imaging probes, demonstrating preliminary capabilities for both lateral imaging (e.g., confocal microscopy) and axial imaging, using optical coherence tomography (OCT) as an exemplar. Hair-thin fiber endoscopes hold great promise for biomedical imaging, especially when paired with custom optics. For instance, OCT benefits from fiber facets that generate needle-like Bessel beams with a large depth-of-field (DOF), while wide-field imaging requires shorter DOF and higher lateral resolution. Current devices often rely on direct fabrication on fiber tips, which is incompatible with high-volume planar nano-fabrication necessary for producing low-cost disposable biomedical devices. In this paper, we propose a scalable fabrication approach compatible with semiconductor manufacturing, which also allows for simultaneous transfer of multiple devices onto fibers. We demonstrate this by transferring four planar lenses at once. To prove their imaging abilities, we designed and transferred a Fresnel zone plate, optimized for lateral imaging, and a diffractive axicon, optimized for axial imaging, onto fiber facets. The axicon fiber generates a needle-like Bessel beam with a 350 μm focal depth, retrieving focused images from a standard resolution target over a 150 μm range. We also present a preliminary demonstration of OCT imaging of reflective targets with a commercial system. Finally, we show that this approach supports multi-layer devices, by fabricating a two-layer Fresnel zone plate fiber probe, which exhibits good imaging performance. This method could enable the integration of complex, multi-functional optical structures onto fibers for advanced imaging and sensing applications.